Mammalian SRP receptor switches the Sec61 translocase from Sec62 to SRP-dependent translocation - Jadhav, Bhalchandra; Sinning, Irmgard (Nature Communications, 2015)
Two distinct pathways deliver secretory proteins to the Sec61 protein translocase in the endoplasmic reticulum membrane. The canonical pathway requires the signal recognition particle (SRP) and its cognate receptor (SR), and targets ribosome-associated proteins to the Sec translocase. The SRP-independent pathway requires the Sec translocase-associated ER membrane protein Sec62 and can be uncoupled from translation. Here we show that SR switches translocons to SRP-dependent translocation by displacing Sec62. This activity localizes to the charged linker region between the longin and GTPase domains of SRα. Using truncation variants, crosslinking and translocation assays reveals two elements with distinct functions as follows: one rearranges the translocon, displacing Sec62 from Sec61. A second promotes ribosome binding and is conserved between all eukaryotes. These specific regions in SRα reprogramme the Sec translocon and facilitate recruitment of ribosome-nascent chain complexes. Overall, our study identifies an important function of SR, which mechanistically links two seemingly independent modes of translocation.